Optimasi Produksi Dengan Menggunakan Metode Downhole Water Loop Pada Sumur Horizontal Untuk Reservoir Minyak Berat Dengan Tenaga Pendorong Air - Hesty Fanila (Politeknik Negeri Madura, 2018)
This paper goal is to observe the best performance in modified DWL well and conventional well for optimize combination of flowrate oil production, flowrate drainage and injection temperature by using the optimization software PETROZILLA based on genetic algorithm for heavy oil reservoir with bottom water drive to the horizontal well types. Production procces for heavy oil reservoir with strong bottom water drive will cause water coning has a complex challenge. Produce heavy oil with bottom water drive mechanism to reduce water coning used method Downhole Water Loop. In this study also be seen the influence DWL with additional heater. From the optimization result be obtained that combination of flowrate oil produstion, flowrate drainage and injection temperature in modified DWL well give the cumulative production oil better than in conventional well.